We know \(\displaystyle e^{0} = 1\), but how to prove it?
Considering function \(\displaystyle y = e^{x}\) where \(\displaystyle y = 1\)
\(\displaystyle 1 = e^{x}\) - Solve for \(\displaystyle x\).
\(\displaystyle \ln(1) = \ln(e^{x})\) - Using \(\displaystyle \ln\) to get an ordinary \(\displaystyle x\) from \(\displaystyle e\).
\(\displaystyle 0 = x\)
Plugging back into the equation:
\(\displaystyle 1 = e^{0}\) or \(\displaystyle e^{0} = 1\)
We know \(\displaystyle \ln(1) = 0\), but how to prove it?
Considering function \(\displaystyle y = \ln(x)\) where \(\displaystyle y = 0\)
\(\displaystyle 0 = \ln(x)\) - Solve for \(\displaystyle x\).
\(\displaystyle e^{0} = e^{\ln(x)}\) - Using \(\displaystyle e\) to get an ordinary \(\displaystyle x\) from \(\displaystyle \ln\).
\(\displaystyle 1 = x\)
Plugging back into the equation:
\(\displaystyle 0 = \ln(1)\) or \(\displaystyle \ln(1) = 0\)
Considering function \(\displaystyle y = e^{x}\) where \(\displaystyle y = 1\)
\(\displaystyle 1 = e^{x}\) - Solve for \(\displaystyle x\).
\(\displaystyle \ln(1) = \ln(e^{x})\) - Using \(\displaystyle \ln\) to get an ordinary \(\displaystyle x\) from \(\displaystyle e\).
\(\displaystyle 0 = x\)
Plugging back into the equation:
\(\displaystyle 1 = e^{0}\) or \(\displaystyle e^{0} = 1\)
We know \(\displaystyle \ln(1) = 0\), but how to prove it?
Considering function \(\displaystyle y = \ln(x)\) where \(\displaystyle y = 0\)
\(\displaystyle 0 = \ln(x)\) - Solve for \(\displaystyle x\).
\(\displaystyle e^{0} = e^{\ln(x)}\) - Using \(\displaystyle e\) to get an ordinary \(\displaystyle x\) from \(\displaystyle \ln\).
\(\displaystyle 1 = x\)
Plugging back into the equation:
\(\displaystyle 0 = \ln(1)\) or \(\displaystyle \ln(1) = 0\)
Last edited: